Trees of the Central Valley of Costa Rica: reproduction. Casuarina. - Rojas-Rodríguez, Freddy (2013)
The following issue presents a brief description about the “casuarina” tree (Casuarina equisetifolia L.) including information about its phenology which directly relates to fruit recollection, seed treatment, nursery, and germination processes.